ORAL LEUCOPLAKIA: DIAGNOSTICS AND TREATMENT - Kamilov Khaidar Pazilovich; Kadirbaeva Aliya Arystanovna; Aripova Dilnoza Utkurovna (Modern American Journals, 2025)
Leukoplakia of the oral mucosa (OM) is the most common potentially malignant disease characterized by the appearance of white, non-erasable spots that have no alternative clinical and histological diagnosis. The article presents modern concepts of the etiology, pathogenesis, classification, clinical forms, diagnostics and treatment of leukoplakia. Particular attention is paid to the issues of dysplasia and precancerous potential of the disease. A review of modern approaches to therapy and dispensary observation of patients with this disease is conducted.
Keywords: leukoplakia, oral mucosa, dysplasia, precancerous disease, treatment